Dimensions and categories for a Physical Activity Label for Schools in Europe: a pilot study in Luxembourg - Heck, Sandra; Scheuer, Claude (Acta Universitatis Carolinae. Kinanthropologica, 2020)
In the frame of the European Physical Activity Label for Schools (Eu-PALS, 2020a) project diverse indicators of physical activity, physical education and sport in different European schools have been analysed. As a starting point, this paper is presenting the chosen indicators and comparing them to an already existing physical activity label for schools in Luxembourg. The choice of the quality criteria in the Eu-PALS project, which may lead to the awarding of the label, are further discussed by demonstrating the results of a pilot study at four schools in Luxembourg. This national pilot study shows not only to the participating schools in which areas they might need to improve their activities, but allows also more generally to evaluate the indicators and possibly to improve the choice. Finally, with regard to the topic of the CEREPS Conference 2019 in Prague – “Quality criteria and outcome standards for Physical Education and School Sport” – in the frame of which this study has been presented, it is also discussed whether the project contributes to make criteria and outcome standards of physical education and school sport in Europe visible and comparable.
Keywords: Schools; pohybová aktivita; Physical Education and Training; Motor Activity; Luxembourg; lidé; průzkumy a dotazníky; Lucembursko; Pilot Projects; Surveys and Questionnaires; pilotní projekty; školy; tělesná výchova; Humans